QUESTIONS OF EVALUATION OF POSTNATAL GROWTH IN PRETERM CHILDREN PART 1. GROWTH CHARTS OF PREMATURE BABIES - A. F. Kiosov ("Paediatrician" Publishers LLC, 2013)
Evaluation of the growth of premature children is of great importance in neonatology and pediatrics. Evaluation of the growth is carried out taking into account the corrected age of preterm infants. Correction is performed during the first two years of life. This is especially important for children born before 32-33 weeks of gestation and weighing less than 1500 g. Evaluation of the growth is carried out with the use of growth charts for premature babies. Growth curves contain three measurements: weight, height and head circumference. Today, there are several growth curves. Lubchenco curves (1963), the curves of Babson and Benda (1976) have been used for more than forty decades. Currently, they do not accurately reflect the growth of a premature baby. In recent years, modern growth curves have been developed. Modern curves are developed on the basis of larger groups, taking into account gender differences. Fenton (2003) proposed growth charts for premature babies. They consist of graphs of percentiles of weight, height and head circumference. Graph compares the growth of preterm infants with fetal growth from 22 weeks to 10 weeks of postnatal age. Gender differences have a significant impact on the growth of children. Fenton (2013) established growth curves for girls and boys. Boys have higher weight, height and head circumference than girls. In assessing the growth of the fetus and the baby after birth national and racial differences should be taken into account. The growth curves of the fetus and preterm infant are important for population health assessment and evaluation of individual growth. The growth curves are used to evaluate the child's performance at birth and for the assessment of the growth of the baby after birth. The growth curves are used in intensive care and pediatric units. In order to achieve adequate growth it is necessary to carry out the correction of regimen, nursing and nutrition of a child.